Study of plant physiological parameters in winter oilseed rape (Brassica napus var. napus f. biennis L.) production on chernozem soil - Vincze, Éva; Pepó, Péter (Acta Agraria Debreceniensis, 2016)
We made plant physiology examinations in Arkaso winter oilseed rape hybrid substance: relative chlorophyll content (SPAD) and leaf area index (LAI) measurements. The experiment was set in University of Debrecen Agricultural Sciences Center at Látóképi Experimental Station in four replications, in two different sowing times (I. sowing date on 08/22/2014 and II. sowing date on 09/09/2014 sowing againhappened because of the incomplete germination in the second subtance 01/10/2014) Three different plant density 200, 350 and 500 thousand ha-1, under the same nutrient supply, 45 cm row spacing. The experiment was green crop of winter wheat. The relative chlorophyll content (SPAD) and leaf area index (LAI) measurements were made in seven different times. We measured the maximum value of chlorophyll content in the first sowing time at 500, and the second sowing time at 350 thousand ha-1 plant density. The measurement results proved that there was a linear relationship between the number of plants and the LAI. The maximum leaf area index values we measured in both the sowing time at 500 thousand ha-1 reached.